Proximity Porosity and Crystallinity Analysis as Clay/Nickel Slag Characteristics for Material Stabilization Application - Gaus, Abdul; Rauf, Ichsan; Siregar, Fahmi; Heryanto, Heryanto (Trends in Sciences, 2024)
Slag nikel is a by-product of nickel ore smelting through the pyrometallurgical process, which contains silica (> 50 %). This suggests that nickel slag, possessing pozzolanic properties, which potentially to be used as a binding material in construction projects dealing with low soil bearing capacity, such as soil improvement for road foundation. Pozzolanic reactions are greatly influenced by the chemical bonds formed between the binding material and the soil, causing mechanical characteristic changes in the soil. This study aims to examine the effect of adding nickel slag to soft soil based on changes in its physical, mechanical and chemical properties. Physical and mechanical property tests were conducted according to ASTM standards, while the changes in chemical structure in the soil were analyzed based on X-Ray Diffraction (XRD) test results. In this study, nickel slag percentages of 3, 6, 9 and 12 % were used based on the weight ratio of clay soil, at optimum water content (wopt). Furthermore, the test specimens were cured for 14, 28 and 56 days to observe the effect of time on the increase of crystal phases in each variation. The results showed that the presence of nickel slag in the soil can affect its physical and mechanical properties. The nickel slag content in the soil of 3, 6, 9 and 12 % reduces the plasticity index by 16.69, 12.02, 8.86 and 6.38 %, respectively. Meanwhile, the density values increased by 10.97, 11.27, 11.68 and 12.01 kN/m3, respectively. The changes in physical and mechanical properties can be explained by the XRD analysis results, showing changes in the spectrum curve and peak intensity of X-Ray Diffraction in the soil with the addition of nickel slag. This explanation clarifies the transformation of the soil’s atomic structure from an amorphous state to a crystalline form, which is stabilized by nickel slag. HIGHLIGHTS The silica-rich nature of nickel slag offers a feasible alternative for chemical soil stabilisation The stabilization of soft soil with nickel slag results in a decrease in the plasticity index and an increase in density Immersion duration shows a changing response for the crystallinity index and porosity of the material GRAPHICAL ABSTRACT